Validation of accelerometer data for measuring impacts during jumping and landing tasks - Gastin, P.; Aisbett, B.; Netto, K.; Tran, J. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
The purpose of this study was to examine the validity of a commercially-available accelerometer, as used in the field team sports context. Ten adult participants completed two movement tasks: 1) a drop landing task from 30-cm, 40-cm and 50-cm heights [DLAND], and 2) a countermovement jumping task [CMJ]. Peak acceleration values, both smoothed and unsmoothed, occurring in the longitudinal axis [Y] and calculated to produce vector magnitude values [VM], were compared to peak vertical ground reaction force values [VGRF]. All acceleration measures were moderately correlated (r = 0.45 - 0.70), but also significantly higher than weight-adjusted VGRF, for both tasks. Though the raw acceleration measures were mostly above the acceptable limit for error (> 20%), the smoothed data had reduced error margins by comparison, most of which were well below 20%. These results provide some support for the continued use of accelerometer data, particularly when smoothed, to accurately quantify impacts in the field.